Samorząd zawodowy adwokatów w opinii jego członków - ANTKOWIAK, Paweł (Przegląd Politologiczny, 2018)
The model of public administration which emerged in Poland after 1989 assumes that its tasks are performed by the apparatus of the centralized government administration as well as by a diversified system of bodies or institutions that operate independently and fulfill public tasks, vested in them by virtue of law, in their own names and on their own accounts. Administrative tasks are performed by obligatory units and by the professional self-governing bodies, among other entities. They play a very important role in the system of representing defined so- cial groups’ interests because they are set up by the professions whose social significance re- quires the highest vocational and moral qualifications. The Chamber of Lawyers is worthy of particular attention, with its rich history and the fact that it forms the kernel of several corpora- tions of professions of public trust. However, recently there are increasing concerns about the justification for such structures and their operation in the public realm. Professional self-governing bodies are being subjected to social and media criticism, and are also criticized by their own members. The main accusa- tion of the representatives of a given profession concerns the apparent clash of their group’s interests with the social interest. All these doubts have resulted in a clear tendency of the progressive limitation of the com- petences of professional self-governing bodies in Poland and their takeover by the state ad- ministration. Several decades of self-government experience is a sufficient period to reveal the shortcomings of a given organization and to demonstrate the need to critically review cur- rent solutions. It is beyond doubt, however, that such a review should be performed by those who are most concerned with the development of a given profession, that is, by the members of a given professional self-governing body. For this purpose a questionnaire has been carried out with the approval of the Supreme Bar Council and with assistance from its officers. The purpose was to answer the question of what is the actual assessment of the work of the Chamber of Lawyers by the members of this pro- fession? The survey results show that lawyers have extensive knowledge of how their own professional self-governing body works. Although the general conclusions are mostly posi- tive, lawyers indicate numerous fields where changes should be introduced. It is clear that self-government has become an inherent part of this profession. Lawyers deem the existence of their professional self-government to be an institution required not only by themselves, but also by social interest.